2002
DOI: 10.1128/iai.70.10.5556-5561.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Bovine Macrophages toMycobacterium aviumsubsp.paratuberculosisandMycobacterium aviumsubsp.avium

Abstract: Mycobacterium avium subsp. paratuberculosis and Mycobacterium avium subsp. avium are antigenically and genetically similar organisms; however, they differ in their virulence for cattle. M. avium subsp. paratuberculosis causes a chronic intestinal infection leading to a chronic wasting disease termed paratuberculosis or Johne's disease, whereas M. avium subsp. avium causes only a transient infection. We compared the response of bovine monocyte-derived macrophages to ingestion of M. avium subsp. paratuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 30 publications
10
115
3
1
Order By: Relevance
“…hominissuis and M. avium subsp. paratuberculosis, as observed previously (55). This previous suggestion is supported by previous observations that a specific M. avium subsp.…”
Section: Discussionsupporting
confidence: 80%
“…hominissuis and M. avium subsp. paratuberculosis, as observed previously (55). This previous suggestion is supported by previous observations that a specific M. avium subsp.…”
Section: Discussionsupporting
confidence: 80%
“…Until now, a lot of researchers have done the study on the mononuclear phagocytes of monocytes and macrophages (14)(15)(16)(17), however, TLRs expression pattern differences between them were few reported. Previous studies have shown that bovine TLRs are differentially expressed in variety of tissues (4).…”
Section: Discussionmentioning
confidence: 99%
“…Disease development appears to be linked with local loss of CD4 C T-cells and gd T-cells (Chiodini 1996;Koets et al 2002). The fundamental defect that could be connected with a reduction in CMI response is the deregulation in MAP-mediated macrophage function (Tooker et al 2002;Weiss et al 2002;Zur et al 2003). Interruption in gene activation and signalling breakdown in the immune response are responsible for controlling MAP infection through genes encoding tumour necrosis factor alpha (TNF-a), interleukin-1 (IL-1), IL-12, and IFN-g and their receptors (Jouanguy et al 1999;Dorman & Holland 2000;Ottenhoff et al 2000) and this could also affect effector activity of CD8 C T-cells (Canaday et al 2001).…”
Section: Immune-based Test Platformsmentioning
confidence: 99%